Conflitos territoriais indígenas no Brasil: entre risco e prevenção / Indigenous land conflicts in Brazil: between risk and prevention - Bragato, Fernanda Frizzo; Neto, Pedro Bigolin (Revista Direito e Práxis, 2017)
DOI: 10.12957/dep.2017.21350 Resumo O artigo objetiva, por um lado, analisar a relação existente entre os direitos indígenas e a garantia de territórios tradicionalmente ocupados à luz dos avanços na legislação nacional e internacional. Por outro lado, analisa em que medida a privação dos territórios aos povos indígenas e os conflitos gerados configuram fatores de risco para crimes de atrocidade, conforme delineado pela ONU no "Framework of Analysis for Atrocity Crimes – A tool for prevention" no âmbito da doutrina da Responsabilidade de Proteger. Palavras-chave: direitos territoriais indígenas; responsabilidade de proteger; crimes de atrocidades. Abstract The article aims, on the one hand, to analyze the existing relationship between indigenous rights and the guarantee of traditionally occupied territories in the light of improvements both in national and international legislation. On the other hand, it analyzes the extent to which deprivation of the territories of indigenous peoples and the generated conflicts constitute risk factors for atrocity crimes, as outlined by the UN in the "Framework of Analysis for Atrocity Crimes - A tool for prevention" within the doctrine of Responsibility to Protect. Keywords: indigenous land rights; responsibility to protect; atrocity crimes.